The Anti-Inflammatory Effect of Octyl Gallate Through Inhibition of Nuclear Factor-κB (NF-κB) Pathway in Rat Endometriosis Model - A Bustami; WP Lestari; CF Hayuningrum; H Wibowo; PE Wuyung; RM Natadisastra (JRI, 2020)
Background: Endometriosis is a chronic inflammatory condition associated with an increased risk of epithelial ovarian cancer. Our previous studies found that the anti-inflammatory effect of octyl gallate in endometriosis cell culture was more effective than gallic acid and heptyl gallate. This study aimed to analyze the anti-inflammatory effect of octyl gallate in rat endometriosis model. Methods: Thirty female Wistar rats were randomly divided into three groups. Group I was the sham-operated group, group II was the surgically-induced group, whereas group III was the surgically-induced group and each rat was administered with 20 mg of octyl gallate dissolved in 1 ml Na-CMC via oral gavage once a day for 30 days. When all rats were euthanized, the endometrial tissue from group I and last two groups were collected for further analysis. TNF-α levels were measured using Luminex, while non-phosphorylated NF-κB and COX-2 levels were analyzed using ELISA.  Results: The average of non-phosphorylated NF-κB levels in group III (4.970±0.971 pg/mgP) was significantly higher than group II (3.97±0.656 pg/mgP). Moreover, the proportion of rats with the high level of non-phosphorylated NF-κB in group III was 45.6% higher than group II (p<0.05). The proportion of rats with the high level of COX-2 in group III was 22.3% lower than group II (p<0.05). However, there was no significant difference in TNF-α levels between all groups.  Conclusion: The anti-inflammatory effect of octyl gallate may has effects in NF-κB activation and reduction of COX-2 levels in rat endometriosis model.